KMT-2021-BLG-1150Lb: Microlensing planet detected through a densely covered planetary-caustic signal - Han, Cheongho; Jung, Youn Kil; Bond, Ian A; Gould, Andrew; Sun-Ju, Chung; Albrow, Michael D; Kyu-Ha Hwang; Yoon-Hyun, Ryu; Shin, In-Gu; Shvartzvald, Yossi; Yang, Hongjing; Yee, Jennifer C; et al. (arXiv.org, 2023)
Recently, there have been reports of various types of degeneracies in the interpretation of planetary signals induced by planetary caustics. In this work, we check whether such degeneracies persist in the case of well-covered signals by analyzing the lensing event KMT-2021-BLG-1150, for which the light curve exhibits a densely and continuously covered short-term anomaly. In order to identify degenerate solutions, we thoroughly investigate the parameter space by conducting dense grid searches for the lensing parameters. We then check the severity of the degeneracy among the identified solutions. We identify a pair of planetary solutions resulting from the well-known inner-outer degeneracy, and find that interpreting the anomaly is not subject to any degeneracy other than the inner-outer degeneracy. The measured parameters of the planet separation (normalized to the Einstein radius) and mass ratio between the lens components are \((s, q)_{\rm in}\sim (1.297, 1.10× 10^{-3})\) for the inner solution and \((s, q)_{\rm out}\sim (1.242, 1.15× 10^{-3})\) for the outer solution. According to a Bayesian estimation, the lens is a planetary system consisting of a planet with a mass \(M_{\rm p}=0.88^{+0.38}_{-0.36}~M_{\rm J}\) and its host with a mass \(M_{\rm h}=0.73^{+0.32}_{-0.30}~M_\odot\) lying toward the Galactic center at a distance \(D_{\rm L} =3.8^{+1.3}_{-1.2}\)~kpc. By conducting analyses using mock data sets prepared to mimic those obtained with data gaps and under various observational cadences, it is found that gaps in data can result in various degenerate solutions, while the observational cadence does not pose a serious degeneracy problem as long as the anomaly feature can be delineated.